3(7v+4)-8v=-2(-v-4)+7v

Simple and best practice solution for 3(7v+4)-8v=-2(-v-4)+7v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(7v+4)-8v=-2(-v-4)+7v equation:



3(7v+4)-8v=-2(-v-4)+7v
We move all terms to the left:
3(7v+4)-8v-(-2(-v-4)+7v)=0
We add all the numbers together, and all the variables
3(7v+4)-8v-(-2(-1v-4)+7v)=0
We add all the numbers together, and all the variables
-8v+3(7v+4)-(-2(-1v-4)+7v)=0
We multiply parentheses
-8v+21v-(-2(-1v-4)+7v)+12=0
We calculate terms in parentheses: -(-2(-1v-4)+7v), so:
-2(-1v-4)+7v
We add all the numbers together, and all the variables
7v-2(-1v-4)
We multiply parentheses
7v+2v+8
We add all the numbers together, and all the variables
9v+8
Back to the equation:
-(9v+8)
We add all the numbers together, and all the variables
13v-(9v+8)+12=0
We get rid of parentheses
13v-9v-8+12=0
We add all the numbers together, and all the variables
4v+4=0
We move all terms containing v to the left, all other terms to the right
4v=-4
v=-4/4
v=-1

See similar equations:

| 3x=x12 | | 5x-7(3x-7)=-47 | | 2(7+5)=2(x+4x-3) | | 30x+2,600=50x+2,400 | | 38=3u+14 | | -9-2(3.2x-9)+2x=-4.9x | | 5x-9x-11=-4x+6-11 | | 6p-2p+4p=32 | | y=(3-6+3) | | -95=-6x-5(4x-7) | | 6-y=63 | | 6-(-3.6x-5.6)-7.5x=-4 | | 2+5x-5=3(x-2 | | 5/6c−1/6c=2 | | x=(5+10-15) | | 5x+2(x-9)=52 | | x+9=171 | | x+21=2x+3 | | c-20=-c | | -6m+4=7-3m | | 14x-(6x-7)=39 | | -10x+2x=16 | | 70-5z=20 | | -92=-2x+2(-3x-6) | | 5y-26=-2(y+6) | | 8x+1=6x-1 | | 2x+6x+5x=26 | | 16c-24=-144 | | 0.9k+0.5k=7 | | |1+6x|=29 | | 3=5b-4b | | -4x+6(x-9)=-42 |

Equations solver categories